The use of mathematical modeling in architectural design to provide sustainable housing - AMR ZEINA (Port Said Engineering Research Journal, 2022)
The research deals with the problem of housing in developing countries, especially the increasing costs of constructing housing units and the inability of governments to provide adequate housing for citizens. The research works to find a way to help reduce construction costs, taking into account design standards and user requirements, by studying the concept of housing in Egypt, its types and development and the role of the state in providing sufficient and sustainable housing that meets the needs and aspirations of users, reviewing the design criteria according to the Unified Egyptian Building Code to ensure that housing projects meet the needs of users, and how to achieve sustainable housing by learning about the concept of sustainability and its principles.The research used the inductive approach to build a mathematical model using linear programming aimed at reducing the wasted spaces within the housing unit and thus reducing construction costs, and then using the experimental method to apply and test the mathematical model on one of the government housing models "Dar Misr" in order to evaluate it.The research helped provide a tool that helps architectural designers in designing and evaluating sustainable housing projects, which reduce construction costs taking into account the design criteria required for the housing unit.